PEMETAAN KESESUAIAN HABITAT JENIS KANTONG SEMAR (NEPENTHES SPP) DI JALUR PENDAKIAN ROREKAUTIMBU SULAWESI TENGAH - Sanggur, Yusuf Godefrianus; Akhbar, Akhbar; Muis, Hasriani (Universitas Tadulako, 2019)
Efforts to preserve semar bag plant species are absolutely necessary so that their existence is maintained. However, the problem faced is limited data and information on habitat factors and the suitability of Semar bag habitats that are most suitable as Semar bag plants. This research was conducted for 3 (three) months from March to May 2018, which is located in the Rorekautimbu Mountain Climbing Route in Central Sulawesi, using a purposive sampling method based on the height of the research location where the height of the research pathway starts from 1,700 m.dpl to 2,500 m.dpl. The height of the mountain was then made into three classes with an altitude of 1,700 masl-1,950 masl, 1,950 masl-2,200 masl and> 2,200 masl. The parameters used to find the suitability of Nepenthes spp habitat are height, slope, vegetation density, and distance from the river. From the results of the research and spatial analysis of all the variables, it can be seen that the most suitable habitat of Nepenthes is in class 238-325 with a total of 43 Nepenthes and an area of 388 Ha, quite appropriate to be in the 149-237 class with a total of 5 Nepenthes and the area reaches 654 Ha, while the less suitable are in the 60-148 class with an area of 72 Ha.Keywords: Habitat, Semar Bags (Nepenthes Spp) and Rorekautimbu